PENGARUH DAYA LAMPU ULTRAVIOLET LIGHT EMITTING DIODE (LED) GROWTH TERHADAP PERTUMBUHAN FISIKA TANAMAN SELADA SISTEM HIDROPONIK - Elisha Zakiyah; Trapsilo Prihandono; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2023)
Lettuce is a horticultural crop that has many enthusiasts and is widely cultivated using hydroponic systems. One important factor for plant growth is the need for sufficient light to support the process of photosynthesis. Efforts to overcome the lack of light is to use artificial light that comes from LED lights. This study aims to determine the effect of ultraviolet LED growth lamp power on the growth of lettuce plants. This study was divided into two groups: the control group without irradiating LED growth lamps and the experimental group using irradiation of LED growth lamps with a duration of irradiation of 4 hours at night. Parameters observed included plant height, leaf length, leaf width, number of leaves and leaf color in the third week. Analysis of research data used a non-parametric statistical test, namely the Kruskal Wallis test with the help of SPSS 23. The results showed that the power treatment of LED growth lamps had a significant effect on plant height, leaf length, leaf width and number of leaves. However, the power treatment of LED growth lamps did not significantly affect leaf color. The results showed that the best treatment was obtained at 18 watts of power.